Assessing the Implementation of Technology Professional Development - Barnes, Jhondra (Valdosta State University, 2005)
The purpose of this action research study was to determine if providing ongoing technology support to teachers after initial technology training increased the use of instructional technology in the classroom. Teachers, who participated in the study, worked in learning teams and with peer coaches to develop technology lessons to use in the classrooms. Eight participants completed all activities.
Keywords: Ongoing Technology Support; Educational technology; Teaching--Aids and devices